2021
DOI: 10.3390/insects12070594
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gut Bacteria on the Physiology of Red Palm Weevil, Rhynchophorus ferrugineus Olivier and Their Potential for the Control of This Pest

Abstract: Red Palm Weevil (RPW), Rhynchophorus ferrugineus Olivier, is a notorious pest, which infests palm trees and has caused great economic losses worldwide. At present, insecticide applications are still the main way to control this pest. However, pesticide resistance has been detected in the field populations of RPW. Thus, future management strategies based on the novel association biological control need be developed. Recent studies have shown that the intestinal tract of RPW is often colonized by multiple microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Additionally, insecticide resistance has been reported for decades, including in RPW populations [ 27 , 28 ]. In lieu of conventional methods, a series of ideas have been implemented to help eradicate the RPW and enable the survival of palm trees [ 29 ]. The Canary Islands of Spain have successfully eradicated red palm weevils using a series of scientifically-based programs supported by adequate resources [ 30 ].…”
Section: R Ferrugineus Is the Most Damaging Insect Pest Of P...mentioning
confidence: 99%
“…Additionally, insecticide resistance has been reported for decades, including in RPW populations [ 27 , 28 ]. In lieu of conventional methods, a series of ideas have been implemented to help eradicate the RPW and enable the survival of palm trees [ 29 ]. The Canary Islands of Spain have successfully eradicated red palm weevils using a series of scientifically-based programs supported by adequate resources [ 30 ].…”
Section: R Ferrugineus Is the Most Damaging Insect Pest Of P...mentioning
confidence: 99%
“…It has been shown that the Drosophila intestinal clearance response to viruses relies on gut commensal bacteria to initiate the Imd signaling pathway as a means of activating the ERK signaling pathway in the gut [ 95 ]. Recent studies have also shown that the long red cone midge Rhodnius prolixus significantly enhances the immune response of the gut upon antibiotic treatment to remove intestinal bacteria by recolonizing S. marcescens or Rhodococcus rhodnii [ 96 , 97 ]. Ordinarily, intestinal commensal bacteria can protect the host by altering physiological functions, pH, and digestive enzyme levels in the gut and can also eliminate pathogens by competing with them for space and nutrients or by producing antibacterial substances [ 59 ].…”
Section: Gut Microbesmentioning
confidence: 99%
“…Larvae fed with different diets could be associated with different microbial communities in the gut. Gut microbes are correlated with host nutrient metabolism, supplementation of essential amino acids, and immunity [22][23][24][25] . The present study hypothesizes that S. exigua larval gut microbes are associated with host cannibalistic behavior.…”
Section: Introductionmentioning
confidence: 99%